The bioethics of genome editing in livestock - Lopes, Filipa Sentieiro de Sousa (2020)
Recently, a host of genome editing technologies have emerged that can edit the genome with progressively increasing efficiency and ease of use. These technologies are based on the use of sequence-specific engineered nucleases, like zinc finger nucleases (ZFN), meganucleases and transcription activator-like effector nucleases (TALEN). Genome editing has been revolutionized, in recent years, with the emergence of clustered regularly interspaced palindromic repeats (CRISPR) and associated protein 9 (Cas9). Consequently, there have been new applications of these genome editing technologies. These genome editing technologies have a huge range of possible applications in livestock welfare, health, productivity, disease resistance, enhance food to human health. These technologies and their applications have sparked both enthusiasm and worry, raising new questions on ethics and governance and generating many debates all over the world. The present work has, therefore, aimed to analyse the ethical issues raised through genome editing applications in livestock and how bioethics could contribute to the search for recommendations in scientific research in the area of genome editing. For this, a literature review based on methodology Preferred Report Items for Systematic Reviews and Meta-Analyzes (PRISMA) was made, in order to understand the state of the art. Issues like ethics, legal and social implications were raised. However, it seems necessary to carry out a revision of the regulatory framework or a boundary definition in order to better clarify the purpose and the limits of the use of this technology. In addition, defining a risk assessment and management procedure, as well as the public acceptance, are important factors for a higher integration of genome editing in our society. In conclusion, genome editing in livestock for all the applied purposes must be considered with prudence and caution until the risks have been rigorously characterised and answered, as well as the public has been properly informed and consulted.